Impact of self-assembly on the photovoltaic properties of a small molecule oligothiophene donor. (1st January 2020) - Hundal, Amanpreet Kaur; Agarwal, Anubha; Jameel, Mohammed A.; Ali, Salman; Chen, Jing-Yu; Kaur, Navneet; Jones, Lathe; Li, Jing-Liang; Langford, Steven J.; Gupta, Akhil
Graphical abstract: Highlights: Positive impact of self-assembly on the photovoltaic performance is demonstrated. Study of the donor-π-acceptor oligothiophene comprising barbituric acid. Note of hydrogen-bonded supramolecular-array of barbiturated-oligothiophene via SEM. Efficiency enhancement by 50% due to self-assembly approach. Device outcome strongly supports the impact of self-assembly in BHJ devices. Abstract: The positive impact of self-assembly on the photovoltaic properties of a donor-π-acceptor oligothiophene molecule coded as CP3, which contains a barbituric acid as a terminal acceptor unit and triphenylamine as donor, enabling hydrogen-bonded spherulites to assemble in its films is described. The hydrogen-bonded supramolecular array of barbiturated-oligothiophene molecules were directly visualized by scanning electron microscopy. Bulk-heterojunction solar cells comprising CP3 and the fullerene PC61 BM show a power conversion efficiency of 6.31%, which is markedly higher than a structural analogue CP4, which comprises a N -ethylrhodanine terminal acceptor unit incapable of participating in the same degree of self-assembly, supporting the impact of self-assembly in BHJ devices.